Implementation Of Safety Equipment Regulations On The Tourism Ship Km. Princess Flower Dadar And Km. From Nature - Noor Sulistiyono; Oktrianti Diani; Leonardo Anugrah Panjaitan (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2022)
Palembang is the capital city of South Sumatra Province, geographically the city of Palembang is divided by the Musi river into two parts, namely across the ilir in the north and across the ulu in the south. There is the Ampera Bridge which is the icon of the city of Palembang which is in the middle of these two areas. This provides many benefits for the city of Palembang, so the city government tries to maximize the potential of utilizing the Musi river to improve the welfare of the people of Palembang City. Sailing safety is a condition in a safe condition. To achieve this, supervision of ship operators can be carried out, while shipping safety is defined as a condition where safety and security requirements are met when sailing. Safety equipment on the KM tourism boat. Segentar nature is needed both in terms of quantity and condition, because this ship is classified as an old ship that is still operating. And the existing condition of safety equipment on the ship KM.Putri Kembang Dadar currently many have been damaged, and have not been updated, while safety equipment is very important to support the safety of passengers boarding parawista ships.